Schamberg’s Disease: A Comprehensive Review - Mataczyńska, Anna; Paprocki, Michał; Dobosz, Mateusz; Arciszewska, Klaudia; Padkowska, Aleksandra; Pieniążek, Jakub Maciej; Skibińska, Justyna; Szpernalowska, Anna (Quality in Sport, 2024)
Schamberg’s disease, also known as progressive pigmented vasculitis, is a rare, chronic skin disorder characterized by petechiae and brown spots, mainly on the lower extremities. In this review article, we provide a detailed overview of Schamberg’s disease. We review its causes, pathogenesis, and histopathological features. We also describe the clinical presentation, diagnostic methods, and treatment options. We emphasize the crucial role of a multidisciplinary approach in the treatment of this condition. We also emphasize the need for further research to better understand the mechanisms underlying Schamberg’s disease. This could lead to the development of more targeted therapies in the future.